2017 Infectious Diseases Society of America Clinical Practice Guidelines for the Diagnosis and Management of Infectious Diarrhea. (19th October 2017) - Shane, Andi L; Mody, Rajal K; Crump, John A; Tarr, Phillip I; Steiner, Theodore S; Kotloff, Karen; Langley, Joanne M; Wanke, Christine; Warren, Cirle Alcantara; Cheng, Allen C; Cantey, Joseph; Pickering, Larry K
Abstract: These guidelines are intended for use by healthcare professionals who care for children and adults with suspected or confirmed infectious diarrhea. They are not intended to replace physician judgement regarding specific patients or clinical or public health situations. This document does not provide detailed recommendations on infection prevention and control aspects related to infectious diarrhea.